'Do not judge others, and you will not be judged' – Fritz Bauer on the potential and responsibilities of human justice. Issue 3 (September 2020) - Bárd, Károly
This article, besides evoking the exceptional achievements of the legendary Hesse Chief Prosecutor Fritz Bauer and reminding us of his legacy, sets out to identify the interrelationships in his life's work and also to reveal the tensions and contradictions between them, both ostensible and real. Besides identifying the interconnections between the different elements of Bauer's overall project, I will show how, in his own perception, cracks began to show in all the components of his overarching program.